Globalization: implications for firms in Germany - Kiel Centre for Globalization, Kiel; Görg, Holger; Hanley, Aoife (Kiel, 2017)
"This paper, however, is not about evaluating whether or not Germany has, on aggregate, done well out of globalization. Rather, we dig deeper into the economy and acknowledge the fact that it is not countries that trade or invest, but rather firms. We therefore look at data at the micro (firm or establishment) level to shed light on questions such as: What types of firms are involved in trade or investments? What distinguishes these globalized firms, if anything, from firms that are not engaged in these international activities? What benefits are there for the firms and also their workers?"